Treatment of multidrug-resistant Pseudomonas aeruginosa bacteremia using ceftolozane-tazobactam-based or colistin-based antibiotic regimens: A multicenter retrospective study - Hakeam A. Hakeam; Ghadi Askar; Khalid Al Sulaiman; Reem Mansour; Maha M. Al Qahtani; Dana Abbara; Nada Aldhayyan; Nariman Dyab; Liyan Afaneh; Muna Islami; Zainab Al Duhailib (Elsevier, 2022)
Background: Ceftolozane-tazobactam is an emerging ‎treatment for severe infections caused by multidrug-resistant (MDR) Pseudomonas ‎aeruginosa. However, limited ‎data support its use in bacteremia treatment. This study aimed to assess the effectiveness of the treatment of MDR P. aeruginosa bacteremia using ceftolozane-‎tazobactam-based or colistin-based regimens. ‎ Patients and methods: This retrospective, cohort, multicentre study included adult patients with ‎MDR P. aeruginosa bacteremia treated with either ceftolozane-tazobactam or ‎colistin, between September 2018 and August 2021, at four hospitals in Saudi ‎Arabia. The primary endpoint was the 30-day risk-adjusted mortality. Secondary endpoints included the 14-day risk of mortality, bacterial eradication, and clinical ‎success. Cox proportional hazards ‎regression and relative risk estimation were used for analysis, as appropriate. ‎ Results: In total, 46 patients were included; 17 patients received ceftolozane-‎tazobactam-based regimen, and 29 received a colistin-based regimen. There was no association with the use of ‎ceftolozane-tazobactam compared to colistin and the 30-day risk-adjusted mortality ‎‎(hazard ratio [HR] ‎0.58, 95% confidence interval [CI] 0.16-2.13, P = 0.42). Also, the ‎‎14-day risk of mortality and bacterial eradication were not different between the ‎ceftolozane-tazobactam and colistin regimens, HR 2.1, 95% CI 0.42-10.48; P = 0.36; and ‎relative risk (RR) 0.65; 95% CI 0.28-1.52; P = 0.30; respectively. On the other hand, ‎ceftolozane-tazobactam use was associated with higher clinical success than colistin ‎‎(RR 1.84, 95% CI 1.11-3.06: P = 0.021).‎ Conclusion: The risk of mortality of MDR P.aeruginosa bacteremia was ‎similar when treated with ceftolozane-tazobactam-based or colistin-based antimicrobial regimens. A higher clinical success was observed with the ceftolozane-‎tazobactam-based regimen compared to the colistin-based regimen. ‎